EMPIRICAL RESULTS OF TESTING THE ALTMAN MODELS (BANK SECTORS) - A.P. Salina, (Academic Journal of Physical and Chemical Sciences, 2019)
An analysis of this study shows that the classification accuracy can be significantly improved with a country-specific assessment, especially with the use of additional variables. In some country models, the information provided by the additional variables helps to raise the classification accuracy to a higher level. The first multidimensional bankruptcy prediction model was developed by E.I. Altman (1968) from New York. Following this groundbreaking work, a multivariate approach to predicting disruptions has spread around the world to researchers in finance, banking, and credit risk. Failure forecasting models are important tools for bankers, investors, asset managers, rating agencies, and even problem firms themselves. The banking sector as the main provider of financing in the economy is especially interested in minimizing the level of non-performing loans in order to maximize profit from lending activities and reduce their own default risk.